CREATING OF AN INTEGRATED SYSTEM OF CONTROL AND QUALITY MANAGEMENT IN THE PUBLIC CATERING OF THE REGION - Sergey Vladimirovich Novoselov; Larisa Alexandrovna Mayurnikova; Tatyana Andreevna Shcherbakova (Современная наука и инновации)
The results of the research of the catering (OP) in the Kemerovo area show the urgency of improving their activities through the development and implementation of innovative projects. As a basic component for the development of innovation projects appropriate systematization of the main victoriabritish elements in the activity of enterprises OP. The proposed description of a business process, enterprises in the system of the OP "science and education - production - market" for innovative development in the regional context of the public power.